Pengaruh Waktu Penyimpanan Terhadap Hasil Pemeriksaan Kolesterol Total Pada Serum Segar Dan Serum Yang Disimpan Selama 72 Jam Pada Suhu 2-8°C - Christina Natalia; Putu Ayu Parwati; Diah Prihatiningsih (PT. GIAT KONSELING NUSANTARA, 2025)
There are several factors that can affect sample stability such as contamination by bacteria and chemicals, exposure to sunlight, the influence of temperature and metabolism of living cells such as blood cells. So the storage method for blood samples is stored in serum form in a refrigerator with a temperature of 2-8°C, so that serum stability will last for 3-5 days. The purpose of this study was to determine the effect of storage time on the results of total cholesterol examinations in fresh serum and serum stored for 72 hours at a temperature of 2-8°C. The research method used was an experimental method with a cross-sectional approach a nd accidental sampling techniques. Data analysis used the Menn-Whitney test. The results of the study from 30 samples contained 24 samples (79.99%) of fresh serum total cholesterol levels at a temperature of 2-8°C in the normal category against serum sampl e examinations stored for 72 hours in the normal category, while 6 samples (20.01%) of fresh serum total cholesterol levels at a temperature of 2-8°C in the threshold category 1against serum sample examinations stored for 72 hours in the threshold category. The results of the data analysis showed a p-value of 0.000, which means that there is an effect of storage time on the results of total cholesterol examinations in fresh serum and serum stored for 72 hours at a temperature of 2-8°C. The factor that caused this was due to the delay in processing the sample, which resulted in an influence on the results of the study.